The time has come to implement routine outcome monitoring in mental health services across Latin America - Clara Paz; Denisse Dogmanas; Alex Behn; Alex Behn (Frontiers in Public Health)
This perspective highlights the transformative potential of routine outcome monitoring in mental health care and public health, advocating for its adoption in Latin America to enhance data-driven decision-making and service quality across the lifespan. The discussion examines global advancements alongside local efforts to implement routine outcome monitoring, addressing key challenges such as infrastructure limitations, clinician engagement, and the need for contextual adaptations. Central to these efforts are strategies like utilizing digital platforms, fostering political commitment, securing financial investments, and prioritizing person-/patient-centered approaches. By integrating routine outcome monitoring into public health systems, policymakers and practitioners can better monitor mental health trends, allocate resources effectively, and design interventions that address community needs. While significant barriers remain, we urge the adoption of digital routine outcome monitoring solutions in Latin America and call for collaborative efforts to fully realize the potential of routine outcome monitoring in improving both mental health services and broader public health initiatives.